Women and Power Relations in Indonesian Classical Historiography: A Feminist Approach - Adi Wildan Alamsyah (Diponegoro University, 2025)
Classical historiography is frequently recounted in an elitist manner, predominantly emphasizing the contributions of the masculine elite, such as men who ascended to kingship, without adequately considering the roles of individuals behind significant events, particularly the contributions of women. Consequently, there is a need for a revised perspective in the writing of classical history that acknowledges the significant roles of women during the Hindu-Buddhist kingdom era, thereby enabling Indonesian classical historiography to more accurately reflect human experiences. This study employs a feminist approach to examine classical history with a focus on the roles of women. The objective is to develop a new perspective in classical history by utilizing auxiliary theories to enhance historical narratives. The study employs historical research methods, including heuristics, verification, interpretation, and historiography. Through the application of auxiliary approaches such as feminism, new insights have emerged, revealing that women made contributions in classical history that were equally significant as those of men. Notable examples include Gayatri Rajapatni, who played an intellectual role in the prosperity of the Majapahit Kingdom; Tribhuwana Tunggadewi, who maintained Majapahit's hegemony by successfully quelling the Sadeng and Këta rebellions during her reign; and Ratu Sima, whose wisdom was evident in her leadership of the Kalingga Kingdom. The findings of this research can be further explored through the development of additional classical historical research.